Causal Relationship Between Economic Growth and Energy Consumption in Jordan - Ali Matar (Jadara Journal of Social Sciences, 2022)
Due to the current situation of the Jordanian economy, this paper aims to evaluate the impacts of economic growth on energy consumption in a developing country like Jordan, a country with limited resources such as oil, agricultural land, and water. This study is very important since the energy bill reflects a notable share in the GDP for Jordan, especially in the recent decade that witnessed energy bills rising due to different political and financial crisis events. The study investigates the causal relationship between the per capita energy consumption and economic growth (proxied by real gross domestic product per capita in constant prices) over the 1975-2011 period. A Granger causality test is utilized on annual time series data. The results of the study confirm a neutral relationship between real GDP and energy consumption, indicating that per capita increase in economic growth may not cause any perpetual rise in energy consumption in Jordan.